Contraceptive histories: a comparative analysis of switching behaviour in five East African countries - Kisaakye, Peter (Centre for Actuarial Research (CARE), 2019)
Since the inception of family planning programmes in developing countries in the 1960s, crosssectional data show remarkable progress in the adoption of modern methods of contraception. Despite the positive contribution contraception plays in preventing unwanted pregnancies, sexually active women from sub-Saharan Africa continue to grapple with unintended pregnancies, which in some instances, results in unsafe induced abortion, with its attendant risks to maternal health. This thesis uses the most recent (as of January 2017) reproductive calendar data from the Demographic and Health Survey (DHS) programme from five East African countries; Ethiopia (2011), Kenya (2014), Rwanda (2014/15), Tanzania (2015/16), and Uganda (2011), to examine how women use contraception over time. The reproductive calendar data that are collected retrospectively provides a better mechanism to understand the trajectory of how women adopt, and immediately switch, contraception than if current-status data were utilised. Three important findings emerge from the analyses: First, contraceptive use being the most important driver of fertility decline, the slow fertility transition that is evident in the five countries can be largely attributable to limited immediate switching of contraception following discontinuation. Despite this universal observation, the key indicators of immediate switching are largely country-specific, which suggests differences in the way family planning programmes are implemented in these countries. Second, all five countries follow a similar pattern of adopting modern contraception – where the majority of users adopt short-term methods compared to long-acting reversible contraceptives (LARCs). However, the duration of use of short-term methods is observed to be shorter compared to LARCs, implying that LARCs facilitate contraceptive continuation. Last, the analysis of current-status data point to improvements in quality of contraceptive provision, and availability – facilitating increased adoption of modern contraception. However, the results indicate that method information exchange is a key predictor of contraceptive use in all countries, with users of LARCs receiving more information than users of short-term methods. Although family planning programmes have made big strides in recruiting new users, this thesis argues that unintended pregnancy, which often leads to a slow fertility transition, can be prevented once family planning programmes emphasise the benefits of immediately switching, or consistent use of contraception among existing users. Sub-optimal switching of contraception among already existing users is likely to attenuate fertility transition.